2014
DOI: 10.1161/strokeaha.113.004116
|View full text |Cite
|
Sign up to set email alerts
|

Optical Bedside Monitoring of Cerebral Blood Flow in Acute Ischemic Stroke Patients During Head-of-Bed Manipulation

Abstract: Background and Purpose A primary goal of acute ischemic stroke (AIS) management is to maximize perfusion in the affected region and surrounding ischemic penumbra. However, interventions to maximize perfusion, such as flat head-of-bed (HOB) positioning, are currently prescribed empirically. Bedside monitoring of cerebral blood flow (CBF) allows the effects of interventions such as flat HOB to be monitored, and may ultimately be used to guide clinical management. Methods Cerebral perfusion was measured during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
117
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(132 citation statements)
references
References 40 publications
9
117
5
1
Order By: Relevance
“…17 In addition to decreasing brain injury by antioxidant, antiapoptotic, and anti-inflammatory actions, another therapeutic strategy for reducing cerebral ischemic injury is to recover cerebral perfusion, leading to decreased cerebral infarction size and neurologic deficits. 18 Central injection of long-acting GLP-1R agonists in mice stimulated brown adipose tissue thermogenesis through regulation of the hypothalamic ventromedial nucleus. 19 In a longitudinal study involving obese patients with Type 2 diabetes, 1 year of treatment with exenatide and liraglutide increased energy expenditure, 19 suggesting the thermoregulatory effect of GLP-1R activation.…”
Section: Introductionmentioning
confidence: 99%
“…17 In addition to decreasing brain injury by antioxidant, antiapoptotic, and anti-inflammatory actions, another therapeutic strategy for reducing cerebral ischemic injury is to recover cerebral perfusion, leading to decreased cerebral infarction size and neurologic deficits. 18 Central injection of long-acting GLP-1R agonists in mice stimulated brown adipose tissue thermogenesis through regulation of the hypothalamic ventromedial nucleus. 19 In a longitudinal study involving obese patients with Type 2 diabetes, 1 year of treatment with exenatide and liraglutide increased energy expenditure, 19 suggesting the thermoregulatory effect of GLP-1R activation.…”
Section: Introductionmentioning
confidence: 99%
“…In several case series, assumption of upright head posture was associated with clinical progression of neurologic deficits and, conversely, assumption of head flat posture was associated with clinical resolution of neurologic deficits [12,13,21]. More recently, in both transcranial Doppler and diffusion correlation spectroscopy studies, placing patients in a head flat position increased measures of cerebral perfusion by 20% and was associated with immediate neurologic improvement in 15% of patients [11,22]. A systematic meta-analysis of physiologic studies found that placing acute cerebral ischemia patients in a head flat, rather than elevated, position increases flow velocity in the affected MCA [23].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, NIRS can recover information about cortical hemodynamics at the microvasculature, which provides a clearer measure of brain function. NIRS' portability, high temporal resolution, low cost and ease of use make it a suitable tool to be used on several environments, ranging from research laboratory to the patient's bedside, as well as in remote areas (Favilla et al, 2014;Mesquita et al, 2013Mesquita et al, , 2012Mesquita et al, , 2009Sanborn et al, 2015). However, NIRS is limited to probe hemodynamic activity to more superficial regions, since scattered light from deeper structures are absorbed before reaching the detector.…”
Section: Introductionmentioning
confidence: 99%